2016
DOI: 10.1097/meg.0000000000000662
|View full text |Cite
|
Sign up to set email alerts
|

Red blood cell distribution width and globulin, noninvasive indicators of fibrosis and inflammation in chronic hepatitis patients

Abstract: RDW may provide a useful clinical value for predicting liver fibrosis; meanwhile, globulin may provide a useful clinical value for predicting liver inflammation in chronic hepatitis patients with other markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…In patients with chronic hepatitis B (CHB) and liver cirrhosis related to CHB, Huang et al[36] observed that RDW values were high and correlated with the severity of cirrhosis in terms of Child-Pugh scores and model for end-stage liver disease (MELD) scores. Wang et al[37] confirmed these findings by demonstrating that RDW may be useful for predicting liver fibrosis in patients with chronic autoimmune hepatitis and PBC, while globulin value may help assessing liver inflammation (Table 2)[38,39]. Several investigators studied the RDW to platelet ratio (RPR) in liver disorders, and analyzed its efficiency for predicting severity of liver fibrosis and cirrhosis.…”
Section: Role Of Rdw In Liver Disordersmentioning
confidence: 97%
“…In patients with chronic hepatitis B (CHB) and liver cirrhosis related to CHB, Huang et al[36] observed that RDW values were high and correlated with the severity of cirrhosis in terms of Child-Pugh scores and model for end-stage liver disease (MELD) scores. Wang et al[37] confirmed these findings by demonstrating that RDW may be useful for predicting liver fibrosis in patients with chronic autoimmune hepatitis and PBC, while globulin value may help assessing liver inflammation (Table 2)[38,39]. Several investigators studied the RDW to platelet ratio (RPR) in liver disorders, and analyzed its efficiency for predicting severity of liver fibrosis and cirrhosis.…”
Section: Role Of Rdw In Liver Disordersmentioning
confidence: 97%
“…A previous study has reported that the erythrocyte count in peripheral blood was associated with survival after surgery in patients with primary liver cancer (11). Several other studies have reported that the red blood cell distribution width (RDW) may serve as a predictive index for histological severity and a potential prognostic indicator of chronic liver diseases (12)(13)(14). While the mechanism underlying the clinical relevance of erythrocytes in PBC remains elusive, previous studies have indicated that erythroid parameters, including the erythrocyte count, are potential prognostic indicators for PBC (12,13).…”
Section: Introductionmentioning
confidence: 99%
“…The effective and accurate prediction of different levels of liver fibrosis of chronic hepatitis is a prerequisite for estimating the prognosis of disease and developing plans for management. The development of new noninvasive indicators and the construction of new noninvasive models, and the evaluation of new noninvasive indicators and models for predicting different levels of liver fibrosis have been an intensive area of liver fibrosis research . In the past 15 years, much progress has been made in the prediction of different levels of liver fibrosis in chronic hepatitis B (CHB) .…”
Section: Introductionmentioning
confidence: 99%